Single-phase and two-phase heat transfer in microchannels - Xu, Bin (2012)
Microfluidics has attracted great attention over the last decade due to its characteristic supreme miniaturisation and low energy consumption as compared to macroscale fluid mechanics. Heat transfer is a crucial process in microfluidic systems and has a significant effect on flow behaviour. This thesis presents analytical and numerical models of single and two-phase heat transfer in microfluidic systems. Experiments were performed to validate these models. In a single-phase flow, experiments with different configurations including T-shaped, straight and H-shaped microchannels were performed. For the T-shaped microchannel, thermal mixing was investigated. A two dimensional analytical model was presented to describe the thermal mixing process in the microchannel. Experimental investigations on thermal mixing were performed to compare with the theoretical analysis. A three-dimensional numerical simulation was developed to investigate the thermal mixing process in the T-junction zone. The thermal effect on mass mixing was further studied. The effect of power input and flow rate were studied experimentally and numerically. For the straight microchannel, a thermal flow sensor was investigated experimentally and numerically. The operation mode of a constant heater temperature was considered in the experiment. A numerical simulation of conjugate forced convection-conduction heat transfer was employed to study fluid flow and heat transfer in the thermal flow sensor. For the H-shaped microchannel, a counter flow micro-heat exchanger (CFMHE) was investigated both theoretically and experimentally. A two-dimensional analytical model was developed to study the heat transfer processes in the CFMHE. Experiments were conducted with hot and cold fluids entering the microchannel with the same heat capacity rate. A new correlation for Nusselt number is proposed based on the experimental Reynolds number and Prandtl number. Good agreements between analytical, experimental and numerical results were obtained.